Inhibition of DNA hybridization following partial dUTP substitution - Carmody, M W (BioTechniques, 1993)
Carry-over contamination from PCR products can yield persistent false-positive results leading to significant problems in the resolution of true positive results. Commercial kits used in many laboratories help prevent carry-over contamination. We present data on the effects of dUTP substitution on the hybridization properties of amplified DNA using alkaline phosphatase conjugated oligonucleotide probes. We observe a pronounced depression in hybridization signal intensity in some dUTP-substituted PCR products. The magnitude of the decreased hybridization signal intensity appears proportional to both the dUTP concentration in the amplification reaction and the fraction of thymidylate residues in the probe binding site. The hybridization signal is nearly eliminated from PCR products synthesized in the presence of dUTP only and where the probe binding site is particularly rich in thymidylate residues. The decrease in hybridization signal is not always restored with less stringent hybridization conditions. Conditions that permit efficient hybridization and detection of bound probe but do not compromise carry-over protection are discussed